Development of an effective preconcentration strategy for the trace determination of nickel in thyme tea extracts by FeSbO4 nanoparticle-based dispersive solid phase extraction (DSPE) - Buyuk, Muhammed Ali; Serbest, Hakan; Bakirdere, Sezgin (ROYAL SOC CHEMISTRY, 2026)
In the present study, an accurate, rapid and green analytical method based on FeSbO4 nanoparticle-assisted dispersive solid phase extraction (DSPE) was developed to determine trace levels of nickel (Ni) by flame atomic absorption spectrophotometry (FAAS). The fabrication of the FeSbO4 nanoparticles was achieved under hydrothermal synthesis conditions and utilized for the first time as sorbent materials for the preconcentration/separation of Ni ions. A univariate optimization approach was applied to determine the optimal conditions for the extraction parameters. Under the optimal conditions, the limit of detection and the dynamic linear range were found to be 0.81 & micro;g L-1 and between 4.0 and 40 & micro;g L-1, respectively. The sensitivity of FAAS was improved by 137.8-fold. Thyme tea samples were spiked to assess the applicability of FeSbO4-DSPE-FAAS, and the percent recovery results between 84.8% and 120.6% obtained with the matrix matching calibration strategy demonstrated that the developed method is feasible for determining nickel ions in thyme tea and similar matrices with high accuracy. The Eco-Scale index was evaluated to determine the greenness of the developed preconcentration protocol, and a net score of 88 was calculated, indicating excellent environmental characteristics.
Keywords: ANTIMONY; SAMPLES; VANADIUM; SCALE; Chemistry; Food Science & Technology; Spectroscopy